Melania Trump : the model who became first lady - Bryan, Bethany (New York Cavendish Square Publishing, 2018)
Melania Trump began her career as a model and now holds the position of first lady of the United States. As a Slovene American, Melania was born in the former Yugoslavia and became a citizen of the United States in 2006. Her marriage to Donald Trump placed her even more in the spotlight as he campaigned for and won the presidency. In her new role as first lady, Melania considers what social concerns she will address to serve the American public.
Big dreams -- Life of a model -- Finding fame, success, and happiness -- A run at the presidency -- The votes are in -- An unfinished legacy -- Timeline.
Includes bibliographical references and index.
8 - 12 years
105819
Keywords: Trump, Melania -- Juvenile literature; Presidents' spouses -- United States -- Biography -- Juvenile literature